Association between acculturation and body weight status among migrant children in Guangzhou, China: a cross-sectional study. Issue 6 (22nd June 2018) - Huang, Xiaoling; Chen, Wen; Lin, Yanwei; Zhang, Qi; Ling, Li
Abstract : Objective: To assess the association between acculturation and body weight status among internal migrant children in China. Design, setting and participants: A cross-sectional study was conducted among 1154 pairs of migrant children aged 11–17 years and their primary caregivers in Guangzhou, China, from April to May 2016. Measures: Migrant children's body weight status was measured by body mass index. Acculturation was measured by a questionnaire, developed and validated by the research team. The questionnaire had three dimensions with five factors, namely language, social interaction, custom, dressing and diet. Social anxiety was measured by Social Anxiety Scale for Children. Food intake was measured by the food frequency table that was developed from a previous study. Logistic regression was performed to examine the association between acculturation and overweight/obesity while controlling for migrant children's and their caregivers' demographic characteristics, children's social anxiety and food intake. Results: Seventy-six out of 1154 (6.6%) migrant children were overweight, and 36 (3.1%) were obese. The overall prevalence of overweight/obesity was 12.5% in boys, and 6.1% in girls (p<0.001), respectively. The mean scores of acculturation were 41.8 (SD=14.6). Migrant children had the highest level of acculturation in the aspect of dressing (mean=61.7, SD = 16.6), followed by language (mean=47.9, SD=22.3), diet (mean=45.0, SD=18.5), social interaction (mean=42.4, SD=21.3) and custom (mean=27.6, SD=19.2). After controlling for confounding factors, the levels of acculturation was negatively associated with overweight/obesity (adjusted OR (aOR)=0.98, 95% CI 0.97 to 1.00, p=0.030). Furthermore, migrant children who had urban-to-urban migrant caregivers were more likely to be overweight/obese (aOR=2.07, 95% CI 1.16 to 3.69, p=0.014) than their counterparts living with rural-to-urban migrant caregivers. Conclusions: The low levels of acculturation was associated with overweight/obesity among migrant children in Guangzhou, China. Promoting healthy acculturation and social campaign on healthy body weight may help prevent childhood overweight/obesity. Young migrant children, boys and children living with urban-to-urban migrant caregivers should be the target subgroups.